The Analysis of School Arrival Delays Among FA Students in Class XI at Sint Carolus Penfui Catholic High School, Kupang - Leo, Leni Marlina; Nagul, Wens (The Future of Education Journal, 2026)
Education plays a crucial role in developing human resources with character, one of which is through fostering student learning discipline. However, in practice, students still exhibit undisciplined behavior, such as being late to school. This study aims to identify and understand the factors causing student tardiness and address these issues through guidance and counseling services. The study used a descriptive qualitative approach with a case study method for an eleventh-grade student at Sint Carolus Catholic High School in Penfui, Kupang. Data collection techniques included an AKPD questionnaire, observation, interviews, and documentation studies. The results indicate that student tardiness is caused by a combination of internal factors, such as poor time management skills, a habit of waking up late, and excessive gadget use, as well as external factors such as distance from home to school, limited transportation, and family responsibilities. The intervention designed was individual counseling with a behavioristic approach through positive reinforcement, habituation, and behavioral contracts. This study emphasizes the importance of collaboration between guidance counselors, homeroom teachers, and parents in improving student time discipline.